PENGEMBANGAN SISTEM PEMBELAJARAN DALAM IMPLEMENTASI KURIKULUM 2013 MENGGUNAKAN MODEL ADDIE PADA ANAK USIA DINI - Siti Rohaeni (Instruksional, 2020)
The 2013 curriculum implementation gap is not in accordance with government curriculum standards and does not use a scientific approach. The purpose of this study was to find a learning system development model for the implementation of the 2013 curriculum for early childhood education with a focus on using a scientific approach. This study used a Research and Development (R&D) method. Data gathering observation, interview, and documentation. Learning activities carried out by utilizing learning resources outside the classroom using the right strategy of methods of conversation, demonstration, direct practice, and singing methods, can build ideas to express freedom, imagination, and creativity so as to develop moral values of religion, language, social emotional , cognitive, physical motor, and art are good or significant.This can be seen from the results of research evidence at the observation stage before the scientific application of 45%, then in the first stage the implementation of the scientific approach amounted to 67.7% despite an increase of 22.7% of children not able to reach the expected target of 80%, and not yet categorized successfully it needs to be continued in stage II. The results of phase II increased by 24.6% to 92.3%, thus achieving the expected target. The results of this study are expected to be used by principals, teachers, parents, and students, as well as input for further researchers